Mc Sebagai Sutradara Emosi: Meningkatkan Kesan Dramatis pada Acara Pernikahan - Ana Nafisa (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study examines the essential role of the Master of Ceremony (MC) in creating and enhancing the dramatic effect of a wedding ceremony by examining the MC as an “emotional director.” The background to this study is the lack of understanding and application of dramaturgy techniques by MCs, which results in wedding ceremonies feeling flat and unimpressive. The objectives of this study are to analyze the strategies used by MCs in applying dramaturgical techniques to create dramatic impressions, identify effective MCs as “emotional directors,” and improve the quality of the emotional experience for the bride and groom and their guests. This study adopts a qualitative approach with a case study design. Informants were selected through purposive sampling, including brides and grooms, wedding organizers, professional MCs, and guests, with the number determined until data saturation was reached. Primary data was collected through in-depth interviews and field observations, while secondary data was obtained from event documentation and academic literature. Data analysis used thematic analysis methods, including transcription, pattern identification, coding, and data synthesis. The results showed that professional MCs had a significant influence on the smooth running and emotional atmosphere of the event, with a very high success rate (90-95%). The MC's public speaking, rhetoric, and impression management skills proved crucial in orchestrating the audience's emotions. In conclusion, the MC acts as a flow controller and emotional facilitator who ensures a memorable and dramatic wedding experience, although the urgency of its use is contextual.